Photocatalytic antibacterial material and preparation method and application thereof

CN122583028BActive Publication Date: 2026-10-27JILIN JUKE HIGH TECH MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611098992.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-27
Estimated Expiration
2046-07-23

AI Technical Summary

Technical Problem

[0007]为了解决现有聚醚醚酮材料表面生物惰性强、自身缺乏抗菌能力,传统抗菌组分易存在释放依赖、团聚或界面结合不稳定,导致材料难以兼顾高效光催化抗菌性能、使用稳定性和生物安全性的问题,本发明提出了一种光催化抗菌材料及其制备方法及应用

Benefits of technology

1.本发明采用四步法合成2,5-二羟基-3-磺酸基-1,4-苯二甲醛二钠盐,并以聚醚醚酮粉末、CuPc-TA和Dha-SO3H作为结构单元,通过溶剂热法制备CuPc-Dha-COF@PEEK光催化抗菌材料。该方法无需复杂的顺序结晶或多层涂覆工艺,即可在PEEK基体上构筑CuPc-Dha-COF光催化活性结构。其中,CuPc结构能够提供有效的光响应和活性氧产生位点,提高材料的光催化抗菌能力;Dha-SO3H结构中的磺酸基能够改善材料的亲水性和界面作用,并可与PEEK分子链中强极性的酮羰基形成偶极相互作用,从而增强COF活性结构与PEEK基体之间的界面结合稳定性,减少活性组分团聚、迁移或脱落,提高光催化活性位点的有效暴露和利用率,使所得材料对大肠杆菌等细菌表现出更强的抑制和灭杀能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122583028B_ABST
    Figure CN122583028B_ABST
Patent Text Reader

Abstract

The application relates to a kind of photocatalytic antibacterial materials and its preparation method and application, relate to polyether ether ketone composite material technical field, solve the strong surface biological inertia of existing polyether ether ketone material, lack antibacterial ability itself, traditional antibacterial component is easy to exist release dependence, agglomeration or interface combination instability, leading to material difficult to consider high efficient photocatalytic antibacterial performance, stability and biological safety problem.The application adopts four-step method to synthesize 2,5-dihydroxy-3-sulfonic acid-1,4-benzene dimethylaldehyde disodium salt, with polyether ether ketone powder, tetraamino phthalocyanine copper and Dha-SO3H as structural unit, CuPc-Dha-COF@PEEK photocatalytic antibacterial material is prepared by solvothermal method, and the photocatalytic antibacterial rate of escherichia coli and staphylococcus aureus is as high as 99.86% and 99.83%, which can be applied to the field of medical implant materials, medical instrument antibacterial surface, antibacterial protective material, ion exchange membrane material or water treatment antibacterial material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyetheretherketone composite materials, specifically to a photocatalytic antibacterial material, its preparation method, and its application. Background Technology

[0002] Polyaryletherketone (PEK) materials are a class of high-performance engineering plastics whose main chain structure consists of aromatic rings, ether bonds, and ketone groups. Typical examples include polyetheretherketone (PEEK) and polyetherketoneketone (PEKK). Among them, PEEK possesses excellent mechanical strength, heat resistance, chemical corrosion resistance, and biocompatibility, making it valuable for applications in orthopedic implants, dental implants, spinal fusion devices, and other medical devices. However, PEEK materials have low surface energy, insufficient hydrophilicity and bioactivity, and lack inherent antibacterial capabilities. Bacteria easily adhere to their surfaces and form biofilms, increasing the risk of implant-related infections and limiting their further application in medical antibacterial interface materials.

[0003] Existing technologies typically improve the antibacterial properties of polyetheretherketone (PEEK) materials through surface modification or the addition of composite antibacterial components. Examples include introducing metallic antibacterial agents, inorganic photocatalytic particles, or antibacterial coatings onto the PEEK surface. While traditional antibacterial materials such as nano-silver and zinc-based antibacterial components can inhibit bacterial growth to some extent, their antibacterial activity usually depends on the release of metal ions or the exposure of inorganic particles, making them susceptible to variations in release rate, dispersion state, and interfacial stability. Insufficient release limits the antibacterial effect, while excessive release may lead to cytotoxicity or tissue irritation. Furthermore, inorganic particles are prone to aggregation within the polymer matrix, and may migrate, detach, or experience activity degradation during long-term use, making it difficult to simultaneously achieve high antibacterial efficiency, stability, and biosafety.

[0004] Photocatalytic antibacterial technology generates reactive oxygen species by exciting materials under light, which disrupt the bacterial cell membrane, protein, and nucleic acid structures, thereby achieving an antibacterial effect. Compared with systems that rely solely on the release of antibacterial agents, photocatalytic antibacterial materials have advantages such as being antibiotic-free, externally triggerable, and less prone to inducing drug resistance. Existing photocatalytic antibacterial materials mostly employ inorganic semiconductors such as zinc oxide and titanium dioxide, or organic photosensitive molecules. However, inorganic semiconductor materials typically suffer from limitations such as a limited photoresponse range, rapid photogenerated electron-hole recombination, easy particle aggregation, and insufficient interfacial compatibility with polymer matrices. Organic photosensitive components may experience decreased photocatalytic activity due to hydrophobic aggregation or poor fixation, affecting antibacterial efficiency and sustained action.

[0005] Covalent organic frameworks (COFs) possess characteristics such as regular channels, designable structures, tunable functional groups, and modifiable photoelectric properties, making them suitable for constructing photocatalytic antibacterial functional structures. Introducing conjugated photosensitive units such as metal phthalocyanines can improve the visible light absorption and photogenerated carrier transport capabilities of the materials; introducing polar functional groups such as sulfonic acid groups can improve the hydrophilicity, ion transport capabilities, and interfacial interactions with the polymer matrix. Therefore, combining functionalized COFs with polyetheretherketones (PEEKs) holds promise for improving problems such as release dependence, inorganic particle agglomeration, and insufficient interfacial bonding in traditional antibacterial agents. However, existing COFs antibacterial materials are mostly used in powder or independent coating form. Direct application to PEEK matrices still suffers from poor processability, weak interfacial bonding, easy loss of active components, and insufficient exposure of antibacterial active sites. If COFs are introduced solely through physical blending, defects easily form at the composite interface due to the surface inertness and segment rigidity of PEEKs. Using multi-step surface pretreatment or layer-by-layer coating methods increases the complexity of preparation, and the long-term stability of the coating remains difficult to guarantee.

[0006] Therefore, there is an urgent need to develop a composite antibacterial material with polyetheretherketone (PEEK) as the matrix and a functionalized covalent organic framework as the photocatalytic antibacterial active structure, as well as its preparation method. This material should form a stable bond between the photocatalytic active unit, the polar functional group, and the PEEK matrix, while maintaining the inherent mechanical properties and chemical stability of PEEK materials. This would improve the photocatalytic antibacterial ability and stability of the material surface, thus meeting the application needs in the fields of medical implantation, antibacterial protection, and functional interface materials. Summary of the Invention

[0007] To address the issues of existing polyetheretherketone (PEEK) materials exhibiting strong bioinertness and lacking inherent antibacterial capabilities, as well as the tendency of traditional antibacterial components to exhibit release dependence, aggregation, or unstable interfacial bonding, making it difficult to simultaneously achieve efficient photocatalytic antibacterial performance, stability in use, and biosafety, this invention proposes a photocatalytic antibacterial material, its preparation method, and its applications. The technical solution of this invention is as follows: A method for preparing a photocatalytic antibacterial material, characterized by comprising the following preparation steps: S1: The basic salt, 2,5-dihydroxy-1,4-phenylcarboxaldehyde and benzyl bromide are added to the solvent and reacted to give 2,5-bis(benzyloxy)-1,4-terephthalaldehyde; S2: Ethylene glycol and catalyst were added to 2,5-bis(benzyloxy)-1,4-terephthalaldehyde, and the mixture was heated under reflux to obtain 2,5-bis(benzyloxy)-1,4-terephthalaldehyde diacetal; then, an ice-salt bath was performed with stirring, fuming sulfuric acid was added in batches, and the mixture was neutralized with an alkaline aqueous solution to obtain a sodium sulfonate intermediate. S3: Add the catalyst to the methanol solution of the sodium sulfonate intermediate, stir to remove the benzyl and acetal protecting groups, filter, and dry to obtain 2,5-dihydroxy-3-sulfonyl-1,4-phenylenedialdehyde disodium salt (Dha-SO3H). S4: Disodium salt of 2,5-dihydroxy-3-sulfonic acid-1,4-phenylenedialdehyde is mixed with copper tetraaminophthalocyanine (CuPc-TA), and dimethyl sulfoxide (DMSO) is added for ultrasonic dispersion. A regulator is added under stirring conditions to obtain a mixed solution. S5: Add polyether ether ketone powder to the mixed solution, stir, heat to react, centrifuge to collect the precipitate, wash, dry, and obtain the photocatalytic antibacterial material, denoted as CuPc-Dha-COF@PEEK.

[0008] Further, the alkaline salt in S1 is any one or at least two combinations of anhydrous potassium carbonate, anhydrous sodium carbonate, sodium hydride, and cesium carbonate; the solvent is any one or at least two combinations of N,N-dimethylformamide (DMF), acetonitrile, acetone, and tetrahydrofuran; the molar ratio of 2,5-dihydroxy-1,4-phenylenedialdehyde to benzyl bromide is 1:2 to 1:3; the reaction temperature is 60 to 80°C, and the reaction time is 6 to 12 h; the initial concentration of 2,5-dihydroxy-1,4-phenylenedialdehyde in the solvent is 1 to 4 mmol / mL.

[0009] Further, the catalyst in S2 is any one or a combination of at least two of toluenesulfonic acid, pyridine p-toluenesulfonate, and trifluoroacetic acid; the molar ratio of 2,5-dihydroxy-1,4-benzaldehyde to the catalyst is 1:0.05 to 1:0.2.

[0010] Further, in S2, the solvent for heating and reflux is toluene, and the heating and reflux temperature is 110~115℃; the temperature of the ice-salt bath is 0℃, and the time is 0.5~2 h; the stirring speed is 300~1500 rpm, and the time is 2~4 h; the mass fraction of free sulfur trioxide in the fuming sulfuric acid is 15%~30%; and the alkaline aqueous solution is a sodium hydroxide aqueous solution, and the mass fraction of the sodium hydroxide aqueous solution is 10%~50%.

[0011] Further, the catalyst in S3 is any one or a combination of at least two of palladium on carbon (Pd / C), palladium hydroxide / carbon, and palladium black, wherein the mass fraction of palladium metal in the Pd / C catalyst is 10%; the stirring is carried out in a hydrogen atmosphere; and the drying time is 8-12 h.

[0012] Further, the molar ratio of 2,5-dihydroxy-1,4-phenylenedialdehyde to CuPc-TA in S4 is 1:3 to 3:1; the regulator is any one or a combination of at least two of acetic acid, formic acid, and trifluoromethanesulfonic acid; and the volume ratio of the regulator to DMSO is 1:100 to 1000.

[0013] Furthermore, the molar ratio of the polyetheretherketone powder to 2,5-dihydroxy-1,4-benzaldehyde in S5 is 1:0.01~0.03.

[0014] Furthermore, in step S5, the stirring time is 2-4 h, the temperature of the heating reaction is 130-150℃, and the reaction time is 24-72 h; the washing is performed using DMSO and ethanol, and the drying time is 8-16 h at a temperature of 80℃.

[0015] A photocatalytic antibacterial material is prepared by the above-described preparation method.

[0016] One application of the above-mentioned photocatalytic antibacterial material is in the fields of medical implant materials, antibacterial surfaces of medical devices, antibacterial protective materials, ion exchange membrane materials, or water treatment antibacterial materials.

[0017] Compared with existing technologies, this invention solves the problems of strong bioinertness and lack of antibacterial ability of existing polyetheretherketone (PEEK) materials, and the tendency of traditional antibacterial components to exhibit release dependence, aggregation, or unstable interfacial binding, making it difficult for materials to simultaneously achieve efficient photocatalytic antibacterial performance, usage stability, and biosafety. The specific beneficial effects are as follows: 1. This invention employs a four-step method to synthesize disodium 2,5-dihydroxy-3-sulfonic acid-1,4-phenylenedialdehyde, and uses polyetheretherketone powder, CuPc-TA, and Dha-SO3H as structural units to prepare CuPc-Dha-COF@PEEK photocatalytic antibacterial materials via a solvothermal method. This method eliminates the need for complex sequential crystallization or multilayer coating processes, enabling the construction of CuPc-Dha-COF photocatalytic active structures on a PEEK matrix. The CuPc structure provides effective photoresponsiveness and reactive oxygen species generation sites, enhancing the material's photocatalytic antibacterial ability. The sulfonic acid groups in the Dha-SO3H structure improve the material's hydrophilicity and interfacial interactions, and can form dipole interactions with the highly polar ketone carbonyl groups in the PEEK molecular chain. This enhances the interfacial bonding stability between the COF active structure and the PEEK matrix, reduces the aggregation, migration, or detachment of active components, and improves the effective exposure and utilization rate of photocatalytic active sites, resulting in a material exhibiting stronger inhibitory and bactericidal capabilities against bacteria such as Escherichia coli.

[0018] 2. In the CuPc-Dha-COF@PEEK photocatalytic antibacterial material provided by this invention, the CuPc-TA structure has a large π-conjugated system and a metal coordination center, which can enhance the photoresponse capability of the material and promote the generation of reactive oxygen species. The sulfonic acid groups in Dha-SO3H can improve the hydrophilicity of the material surface and the bacterial contact interface, and enhance the interfacial interaction between the COF active structure and the PEEK matrix, so that the photocatalytic active sites can stably and fully exert their antibacterial effect. Therefore, the CuPc-Dha-COF@PEEK provided by this application has excellent photocatalytic antibacterial performance, with photocatalytic antibacterial rates of 99.86% and 99.83% against Escherichia coli and Staphylococcus aureus, respectively. Compared with PEEK-based materials with traditional silver nanoparticle antibacterial agents and nano-ZnO antibacterial components, the rates are increased by 0.29 to 0.33 times. This indicates that this invention can reduce the dependence of traditional metal or inorganic antibacterial systems on ion release, particle dispersion, and interface exposure, and achieve efficient and stable photocatalytic antibacterial effect.

[0019] 3. The preparation process of this invention is relatively mild, enabling effective composite formation of the functionalized COF structure with the PEEK matrix through a solvothermal process. While endowing the material with photocatalytic antibacterial function, it retains the inherent heat resistance, chemical corrosion resistance, and structural stability of PEEK material. The resulting CuPc-Dha-COF@PEEK photocatalytic antibacterial material combines the engineering applicability of the polymer matrix, the functional designability of the COF structure, and photocatalytic antibacterial activity. It can be used in fields such as medical implant materials, antibacterial surfaces of medical devices, antibacterial protective materials, ion exchange membrane materials, or water treatment antibacterial materials, providing a new technical solution for the construction and application of PEEK-based functional antibacterial materials. Attached Figure Description

[0020] Figure 1 The process flow diagram for the synthesis of disodium 2,5-dihydroxy-3-sulfonic acid-1,4-phenylenedialdehyde; Figure 2 The infrared spectrum of disodium 2,5-dihydroxy-3-sulfonic acid-1,4-phenylenedialdehyde. Figure 3 The results show the change in the photocatalytic antibacterial rate of the photocatalytic antibacterial material against Escherichia coli with light exposure time. Figure 4 The results show the photocatalytic antibacterial rate of the photocatalytic antibacterial material against Staphylococcus aureus as a function of light exposure time. Detailed Implementation

[0021] To make the technical solutions of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. It should be noted that the following embodiments are only used to better understand the technical solutions of the present invention and should not be construed as limiting the present invention.

[0022] Example 1. S1: Dissolve 1 mmol of anhydrous potassium carbonate, 1 mmol of 2,5-dihydroxy-1,4-phenylcarboxaldehyde and 2 mmol of benzyl bromide in 1000 mL of DMF and react at 80 °C for 10 h to obtain 2,5-bis(benzyloxy)-1,4-terephthalaldehyde. S2: 200 mL of ethylene glycol and 0.12 mmol of p-toluenesulfonic acid were added to 2,5-bis(benzyloxy)-1,4-terephthalaldehyde, and the mixture was heated under reflux at 110 °C with 200 mL of toluene as solvent to obtain 2,5-bis(benzyloxy)-1,4-terephthalaldehyde diacetal; then, the mixture was subjected to an ice-salt bath and stirred at 1200 rpm for 120 min, and fuming sulfuric acid was added in batches, wherein the mass fraction of free sulfur trioxide in the fuming sulfuric acid was 20%; then, a 20% mass fraction of sodium hydroxide aqueous solution was added for neutralization to obtain a sodium sulfonate intermediate; S3: The sodium sulfonate intermediate was dissolved in 200 mL of methanol, and 33.46 g of Pd / C catalyst (the mass fraction of palladium metal in the Pd / C catalyst was 10%) was added. The mixture was stirred at room temperature (20~25℃), atmospheric pressure (0.08~0.12 MPa), and under a hydrogen atmosphere to remove the benzyl and acetal protecting groups. After filtration and drying for 8 h, 2,5-dihydroxy-3-sulfonic acid-1,4-phenylenedialdehyde disodium salt (Dha-SO3H) was obtained. The synthesis process flow diagram of Dha-SO3H is shown below. Figure 1 As shown; S4: Mix 1 mmol of disodium 2,5-dihydroxy-3-sulfonic-1,4-phenylenedialdehyde with 1.5 mmol of CuPc-TA, add 50 mL of DMSO, sonicate to disperse, and add 1 mL of acetic acid (6 M) under stirring to obtain a mixed solution; S5: Add 100 mmol of polyether ether ketone powder to the mixed solution and stir for 4 h. Transfer the mixed solution to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and react at 150 °C for 72 h. Centrifuge to collect the precipitate, wash it several times with DMSO and ethanol, and then dry it in a vacuum oven at 80 °C for 12 h to obtain the photocatalytic antibacterial material CuPc-Dha-COF@PEEK.

[0023] like Figure 2The image shows the infrared spectrum of Dha-SO3H prepared in Example S3 of this embodiment. As can be seen from the image, at 3350 cm⁻¹... -1 A broad absorption peak appears nearby, attributed to the OH stretching vibration of the phenolic hydroxyl group; at 1500 cm⁻¹... -1 A distinct absorption peak appears nearby, which can be attributed to the characteristic absorption of aromatic ring skeletal vibration and aldehyde C=O stretching vibration; at 1410 cm⁻¹ -1 and 1190cm -1 The characteristic absorption peak of the S=O bond in the sulfonic acid group appears nearby, at 820 cm⁻¹. -1 The presence of a characteristic absorption peak of the SO bond nearby demonstrates that the Dha-SO3H provided in S3 of this application retains structural features such as hydroxyl and aldehyde groups, and successfully introduces a sulfonic acid group structure, indicating that the disodium salt of 2,5-dihydroxy-3-sulfonic acid-1,4-phenylenedialdehyde was successfully synthesized using a four-step method.

[0024] Example 2. The difference between this embodiment and Example 1 is that in S1, the amount of 2,5-dihydroxy-1,4-benzaldehyde is adjusted to 2 mmol and the amount of benzyl bromide is adjusted to 4 mmol; in S4, the amount of acetic acid is adjusted to 2 mL (6 M); the remaining preparation steps and conditions are the same as in Example 1, and CuPc-Dha-COF@PEEK is obtained.

[0025] Example 3. The difference between this embodiment and Example 1 is that in S1, the amount of 2,5-dihydroxy-1,4-benzaldehyde is adjusted to 3 mmol and the amount of benzyl bromide is adjusted to 6 mmol; in S4, the amount of acetic acid is adjusted to 3 mL (6 M); the remaining preparation steps and conditions are the same as in Example 1, and CuPc-Dha-COF@PEEK is obtained.

[0026] Comparative Example 1. S1: 1 mmol of 2,5-dihydroxy-1,4-benzaldehyde and 1.5 mmol of CuPc-TA were ultrasonically dispersed in 50 mL of DMSO, and 0.5 mL of acetic acid (6 M) was added under stirring to obtain a mixed solution; S2: Add 100 mmol of polyether ether ketone powder to the mixed solution and stir for 4 h. Transfer the mixed solution to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and react at 150 °C for 72 h. Centrifuge to collect the precipitate, wash it several times with DMSO and ethanol, and then dry it in a vacuum oven at 80 °C for 12 h to obtain CuPc-Dha-COF@PEEK.

[0027] Comparative Example 2. 30 mg of polyetheretherketone (PEEK) powder was ultrasonically dispersed in 50 mL of AgNO3 (2 M / L) solution and stirred for 2 h to obtain a mixed solution. The mixed solution was transferred to a glass reactor and irradiated under a xenon lamp with a 420 nm cutoff filter for 4 h under vacuum. After centrifugation, the precipitate was obtained. The precipitate was washed 5-6 times with deionized water and ethanol and then transferred to a vacuum drying oven and dried overnight at 80 °C. AgNP@PEEK was obtained.

[0028] Comparative Example 3. 150 mL of NaOH (2.4 mol / L) aqueous solution was slowly added dropwise to 150 mL of ZnSO4 (1.23 mol / L) aqueous solution, and stirred for 4 h to form a 5 wt% homogeneous Zn(OH)2 sol. 100 g of PEEK powder was added in batches to 200 mL of Zn(OH)2 sol, and ultrasonically stirred for 2 h to obtain a mixed sol. The mixed sol was placed in a vacuum drying oven at 160℃ and dried for 72 h to obtain a ZnO@PEEK composite material. The ZnO@PEEK composite material was ground into a fine powder, fed into a twin-screw extruder, and extruded and pelletized at 375℃.

[0029] Antibacterial performance test: Escherichia coli and Staphylococcus aureus were inoculated onto LB agar plates and activated by incubation at 37°C for 24 h. Single colonies were picked and inoculated into liquid culture medium, and cultured with shaking until the logarithmic growth phase. The bacterial suspension was then diluted to 10⁻¹⁰ with sterile physiological saline or PBS buffer. 5 CFU / mL, for later use. Weigh 20 mg of the composite antibacterial material photocatalyst and add it to 20 mL of the above bacterial solution. Place the mixture in a photocatalytic reactor and treat it in the dark for 30 min under magnetic stirring to allow the material and bacterial solution to reach adsorption-desorption equilibrium. Then turn on the light source for irradiation and start timing, taking samples every 30 min. Dilute the samples 10-fold with sterile physiological saline. Take 100 μL of the diluted bacterial solution and spread it evenly on a solid culture medium plate. Invert the plate and incubate it in a 37℃ constant temperature incubator for 24 h. After incubation, select plates with colony counts of 30-300 for colony counting, and calculate the antibacterial rate (%) according to the formula: Antibacterial rate (%) = [(C0-C) / C0]×100%, where C0 is the colony count of the control group (darkness or only light), and C is the colony count of the experimental group. At the same time, plot the time-survival rate curve based on the colony count results at different irradiation times to evaluate the dynamic sterilization efficiency of the composite antibacterial material photocatalyst.

[0030] like Figure 3The figures show the test results of the photocatalytic antibacterial rate of the photocatalytic antibacterial materials prepared in Examples 1-3, the materials prepared in Comparative Examples 1-3, and pure PEEK against Escherichia coli as a function of illumination time. As can be seen from the figures, the antibacterial rate of the pure PEEK group remained consistently low, only slowly increasing from 31.35% to 44.62% with prolonged irradiation time, indicating that PEEK itself lacks effective photocatalytic antibacterial activity. In contrast, the CuPc-Dha-COF@PEEK materials prepared in Examples 1-3 of this application exhibited a high antibacterial rate from the initial stage of illumination, and this rate continued to increase with prolonged irradiation time. Example 1 showed an antibacterial rate as high as 99.86% at 180 min, while Examples 2 and 3 also maintained a high level (both above 95%). This demonstrates that by introducing the CuPc-Dha-COF photocatalytic active structure, this application can significantly improve the inhibitory and killing ability of PEEK-based materials against Escherichia coli. This application describes the use of CuPc-TA and disodium 2,5-dihydroxy-3-sulfonic acid-1,4-phenylenedialdehyde as COF structural units, and the construction of a CuPc-Dha-COF photocatalytic active structure on a PEEK matrix via a solvothermal method. This significantly improves the inhibition and killing ability of PEEK-based materials against *E. coli*. This is because the CuPc structure provides effective photoresponsiveness and reactive oxygen species (ROS) generation sites, while the sulfonic acid groups in the Dha-SO3H structure improve the hydrophilicity and interfacial interactions of the material, and can form dipole interactions with the strongly polar ketone carbonyl groups in the PEEK molecular chain. This enhances the binding stability between the COF active structure and the PEEK matrix, reduces the loss of active components, and improves the effective utilization of photocatalytic active sites. Comparative Example 1, which did not introduce sulfonic acid-modified aldehyde monomers, had a lower antibacterial rate than Examples 1-3, indicating that the sulfonic acid functional unit promotes the improvement of COF structure construction, interfacial interaction, and photocatalytic antibacterial performance. Comparative Examples 2 and 3, which used AgNP@PEEK and ZnO@PEEK respectively, had antibacterial rates higher than pure PEEK, but significantly lower than Examples 1-3, at only 74.94% and 91.38%, respectively. This shows that traditional metal or inorganic oxide antibacterial systems are difficult to achieve the photocatalytic antibacterial effect of the material in this application under the same test conditions.

[0031] like Figure 4The figures show the test results of the photocatalytic antibacterial rate of the photocatalytic antibacterial materials prepared in Examples 1-3, the materials prepared in Comparative Examples 1-3, and pure PEEK against Staphylococcus aureus as a function of irradiation time. As can be seen from the figures, the antibacterial rate of the pure PEEK group against Staphylococcus aureus is low, still less than 50% after 180 min, indicating that the unmodified PEEK material is difficult to effectively inhibit the proliferation of Gram-positive bacteria. The antibacterial rate of Examples 1-3 increases significantly with prolonged irradiation time, reaching a high level at 180 min, with Example 1 showing an antibacterial rate as high as 99.83%, exhibiting excellent photocatalytic antibacterial performance. Compared with Comparative Example 1, Examples 1-3 show a higher antibacterial rate throughout the irradiation process, indicating that the use of disodium 2,5-dihydroxy-3-sulfonic acid-1,4-phenylenedialdehyde in the construction of the COF structure is beneficial for enhancing the hydrophilicity, interfacial bonding, and exposure of active sites, thereby improving the photocatalytic antibacterial efficiency. The antibacterial rates of Comparative Examples 2 and 3 were only 85.75% and 77.14%, respectively, which were significantly lower than those of Examples 1-3. This indicates that the CuPc-Dha-COF@PEEK material constructed in this application has stronger photocatalytic antibacterial activity and more stable antibacterial performance compared with traditional AgNP@PEEK and ZnO@PEEK.

[0032] In summary, this invention employs a four-step method to synthesize disodium 2,5-dihydroxy-3-sulfonic-1,4-phenylenedialdehyde, and uses polyetheretherketone powder, CuPc-TA, and Dha-SO3H as structural units to prepare CuPc-Dha-COF@PEEK photocatalytic antibacterial materials via a solvothermal method. The CuPc structure provides effective photoresponsiveness and reactive oxygen species generation sites, enhancing the photocatalytic antibacterial ability of the material. The sulfonic acid groups in the Dha-SO3H structure improve the hydrophilicity and interfacial interactions of the material, and can form dipole interactions with the strongly polar ketone carbonyl groups in the PEEK molecular chain, thereby enhancing the interfacial bonding stability between the COF active structure and the PEEK matrix, reducing the aggregation, migration, or shedding of active components, and improving the effective exposure and utilization rate of photocatalytic active sites. This results in the material exhibiting stronger inhibitory and bactericidal capabilities against bacteria such as Escherichia coli. The CuPc-Dha-COF@PEEK provided in this application achieves photocatalytic antibacterial rates of 99.86% and 99.83% against Escherichia coli and Staphylococcus aureus, respectively.

[0033] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.

[0034] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a photocatalytic antibacterial material, characterized in that, The preparation steps include the following: S1: The basic salt, 2,5-dihydroxy-1,4-phenylcarboxaldehyde and benzyl bromide are added to the solvent and reacted to give 2,5-bis(benzyloxy)-1,4-terephthalaldehyde; S2: Ethylene glycol and a catalyst were added to 2,5-bis(benzyloxy)-1,4-terephthalaldehyde, and the mixture was heated under reflux to obtain 2,5-bis(benzyloxy)-1,4-terephthalaldehyde diacetal; then, an ice-salt bath was performed with stirring, fuming sulfuric acid was added in batches, and the mixture was neutralized with an alkaline aqueous solution to obtain a sodium sulfonate intermediate. S3: Add catalyst to methanol solution of sodium sulfonate intermediate, stir, filter, and dry to obtain disodium 2,5-dihydroxy-3-sulfonic acid-1,4-phenylenedialdehyde; S4: Disodium salt of 2,5-dihydroxy-3-sulfonic-1,4-phenylenedialdehyde is mixed with copper tetraaminophthalocyanine, and dimethyl sulfoxide is added for ultrasonic dispersion. A regulator is added under stirring to obtain a mixed solution. S5: Add polyether ether ketone powder to the mixed solution, stir, heat to react, centrifuge to collect the precipitate, wash, dry, and obtain the photocatalytic antibacterial material, denoted as CuPc-Dha-COF@PEEK.

2. The method for preparing photocatalytic antibacterial material according to claim 1, characterized in that, The basic salt in S1 is any one or at least a combination of two of anhydrous potassium carbonate, anhydrous sodium carbonate, and cesium carbonate; the solvent is any one or at least a combination of two of N,N-dimethylformamide, acetonitrile, acetone, and tetrahydrofuran; the molar ratio of 2,5-dihydroxy-1,4-benzaldehyde to benzyl bromide is 1:2 to 1:3; the reaction temperature is 60 to 80°C, and the reaction time is 6 to 12 h.

3. The method for preparing photocatalytic antibacterial material according to claim 1, characterized in that, The catalyst in S2 is any one or a combination of at least two of toluenesulfonic acid, pyridine p-toluenesulfonate, and trifluoroacetic acid; the molar ratio of 2,5-dihydroxy-1,4-benzaldehyde to the catalyst is 1:0.05 to 1:0.

2.

4. The method for preparing photocatalytic antibacterial material according to claim 1, characterized in that, The solvent used for heating and reflux in S2 is toluene, and the heating and reflux temperature is 110~115℃; the temperature of the ice-salt bath is 0℃, and the time is 0.5~2 h; the stirring speed is 300~1500 rpm, and the time is 2~4 h; the mass fraction of free sulfur trioxide in the fuming sulfuric acid is 15%~30%; the alkaline aqueous solution is a sodium hydroxide aqueous solution, and the mass fraction of the sodium hydroxide aqueous solution is 10%~50%.

5. The method for preparing photocatalytic antibacterial material according to claim 1, characterized in that, The catalyst in S3 is any one or a combination of at least two of palladium on carbon, palladium hydroxide / carbon, and palladium black, wherein the mass fraction of palladium metal in the palladium on carbon catalyst is 10%; the stirring is carried out in a hydrogen atmosphere; and the drying time is 8-12 h.

6. The method for preparing photocatalytic antibacterial material according to claim 1, characterized in that, The molar ratio of 2,5-dihydroxy-1,4-benzaldehyde to tetraaminophthalocyanine copper in S4 is 1:3 to 3:1; the regulator is any one or at least a combination of two of acetic acid, formic acid, and trifluoromethanesulfonic acid.

7. The method for preparing photocatalytic antibacterial material according to claim 1, characterized in that, The stirring time in S5 is 2-4 h, the temperature of the heating reaction is 130-150℃, and the reaction time is 24-72 h; the washing is performed using DMSO and ethanol, and the drying time is 8-16 h at a temperature of 80℃.

8. A photocatalytic antibacterial material, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.

9. The application of a photocatalytic antibacterial material prepared by the preparation method according to any one of claims 1-7 or the photocatalytic antibacterial material according to claim 8, characterized in that, It is used in the fields of antibacterial surfaces for medical devices or antibacterial materials for water treatment.

Citation Information

Patent Citations

  • Photoelectrochemical material, preparation method and application thereof, and photoelectrochemical biosensor

    CN117624519A

  • Copper phthalocyanine covalent organic framework, composite film, and preparation method and application of copper phthalocyanine covalent organic framework and composite film

    CN119306908A